PHARMACOPHORE BASED SCREENING OF EPICATECHIN AGAINST COLON CANCER (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
The present study deals with Pharmacophore based analog generation of Epicatechin derivatives against the PKC-alpha receptor for treating colon cancer. The chemical features of Epicatechin were analyzed by catalyst - Hiphop algorithm and its derivatives were generated based on Epicatechin Pharmacophore using Minimaybridge commercial database. Two different Epicatechin Pharmacophore analogs were acquired by virtual screening and docked against the PKC-alpha for screening the protein binding affinity. The Pharmacophore result gives HTS01501 possess -3.514 Kcal /mol highest dock score as like as Epicatechin.